MENCEGAH TINDAK KEKERASAN DAN TAWURAN ANTAR PELAJAR MELALUI PENGEMBANGAN PROGRAM PELATIHAN SOCIAL PERSPECTIVE TAKING DI SEKOLAH - Nanik Yuliati (Psympathic : Jurnal Ilmiah Psikologi, 2013)
This writing proposed conceptual idea about psychological interviewing approach preventing violence and fighting. Low of perspective taking in solving problems is viewed as a reason. Developmental approach is considered to be an alternative approach for effective program designed. Perspective taking ability is not inherited but learned. Developmental of perspective taking training program could be an alternative treatment. This program should be preventive and being part of curriculum. .